RELEVANSI NILAI LABA, NILAI BUKU, DAN PENGUNGKAPAN INFORMASI MELALUI WEBSITE PERUSAHAAN - Azhmi, Mohamad Fadhli; Subekti, Imam (Jurnal Ilmiah Mahasiswa FEB, 2014)
This research is aimed to examine the value relevance of  accounting information and the affect of broad information disclosure through company’s website towards value relevance of accounting information. The population of this research are companies listed on Indonesia Stock Exchange (IDX) in 2013. Results of  this  research  indicate  that  there  is  value  relevance of accounting  information among public  companies  in  Indonesia. The  results also  shows  that  the  extent of information disclosure through company’s website  is  able  to  increase  value relevance of earnings.  On  the  other hand,  the  extent  of  information  disclosure through company’s website is unable to increase value relevance of book value. Keywords: Value relevance, earnings, book value, information disclosure.